Hora dourada: avaliação das boas práticas na assistência ao parto e nascimento - GALVÃO, Kayo Elmano Costa da Ponte (2024)
The Golden Hour consists of effective and beneficial newborn care measures that significantly reduce negative consequences in the short and long term, and that require in-depth involvement of professionals. However, some factors end up harming the quality and execution of the golden hour in healthcare institutions. Furthermore, professional interventionist practice also becomes an obstacle in providing care, as many professionals are used to separating mother and baby for routine procedures. It is necessary to strengthen public policies aimed at childbirth and childbirth, with a view to greater qualifications of professionals who are in charge of this process, with the aim of increasingly bringing good practices to maternity wards. The objective of this study was to analyze the good practices associated with the golden hour in labor and birth care. The methodology used was a mixed approach, with quantitative and qualitative elements, with the aim of allowing a more comprehensive and holistic description of phenomena in the social and health fields. In the quantitative approach, data from maternal and neonatal records were collected to identify golden hour achievement rates. To deepen the gaps observed in the quantitative study, phenomenology was used in the qualitative approach, with the purpose of understanding the experiences of health professionals when carrying out the practice. The study was carried out in a public maternity hospital in the state of Maranhão. 180 medical records took part in the study, in addition to an interview with 17 health professionals. It was possible to observe that the golden hour achievement rates differed between the vaginal and cesarean birth scenarios, showing the latter as complicating the practice. Routine separation for initial care, lack of professional encouragement, and neonatal instability were some of the factors affecting care. Health professionals understand the importance of the golden hour, but experience the daily routine and lack of dialogue in care, in order to prioritize medical attitudes to the detriment of female protagonism in the labor and birth process. Thus, it was observed that the implementation of the golden hour proved to be deficient, and that the lack of dialogue and the medicalization of assistance justify this deficiency.